Iklan Layanan Masyarakat dalam Mempengaruhi Opini Publik - Muhamad Gia Galihleo; Nisa ‘Arifatul Umriyah; Novandri Adi Nugroho; Riefky Al Farez; Arfian Suryasuciramdhan (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Public service advertisement (PSA) is one of the mass communication strategies used to convey social messages to the public. The purpose of this study was to analyze the influence of PSA on changes in people's social behavior, especially in environmental and health issues. The results of the study showed that PSA has a significant influence on increasing awareness and changing people's behavior, especially in terms of disposing of waste in its place and reducing the use of single-use plastic.